PENGARUH KEPEMIMPINAN, KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PD. BPR ROKAN HILIR CABANG KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Saputra Erwin; Marnis Marnis; Roesdi Rosnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to see the influence of leadership and job satisfaction on employees performance of PD. BPR Kubu Babussalam Branch, Rokan Hilir Regency. The population in this study were all permanent employees who worked at PD. BPR Rokan Hilir, Kubu Branch, as many as 39 people. Sampling using the census method, namely taking the entire population as the research sample. The data analysis used is descriptive analysis, with quantitative analysis tools, namely multiple linear regression with the help of SPSS version 20.0. Based on the test results it was found that leadership and job satisfaction simultaneously and partially have a positive and significant effect on employee performance. The contribution of the influence of the leadership variables and job satisfaction on employee performance is 70.1%, while the remaining 29.9% is by other variables not included in this model.Keywords: Leadership, Job Satisfaction And Employees Performance